Новий підхід до вирішення задач управління режимами магістральних мереж об'єднаних енергетичних систем - Lenchevsky Ye.A.; Tuwarshiew W.K. (General Energy Institute of the National Academy of Sciences of Ukraine, 2001)
Structural diagram of measuring system of δ1.2 angle between A1(U) and E2(U2) vectors and regulation of modes of station generators 1; 2 are present. The plots of P1;P2; Q1; Q2 and power losses ΔS versus δ1.2 are given. It is shown the relative losses ΔS/Pn dependence of δ1.2 angle regulation from dmin up to dcr. It is illustrated on an example that an variation of δt=δ1.2=60 up to 65(68) will allow an increasing of HVPL load by the factor of 1.5 (2). Present research is a part of design technique under developing of advanced control systems of main power lines modes in the pooled power systems as well as regulation of station's generators and synchronous compensators.